Tinjauan Awal Hubungan Vulkanostratigrafi Dengan Tipe Mineralisasi Daerah Kokap, Kulon Progo, Yogyakarta - Oky Sugarbo (Retii, 2019)
ABSTRACT The Kulonprogo Mountains are mostly Tertiary volcano products that form a high morphology located on the western side of Yogyakarta. Each volcano generally forms volcanic facies and is followed by hypogeneous follow-up processes such as the hydrothermal alteration process that forms ore minerals. This research is a preliminary study to see the relationship between volcanic stratigraphy with the existence of hydrothermal processes and the type of mineralization in the southern Kulon Progo Mountains. The method that used is a qualitative analysis that combines morphology data and data from some previous study so that a comprehensive conclusion can be drawn. The results showed the presence of mineralization with epithermal type and indicate the existence of porphyry systems that associate with volcanic rocks that characterize the central to proximal facies. In the study area there is an indication of the relationship between volcanic stratigraphy and the presence of mineralization types. Mineral deposits that are located far from the indication of the eruption center tend to be of low sulfidation type while approaching the eruption center, the type of mineralization leads to high sulfidation. Mineralization systems in the Hargoejo, Gunung Agung and Kalirejo areas are interpreted to follow the Ijo Crown system while the Sangon Region mineralization system follows the Kukusan Hummock system. Not always high sulfidation epithermal deposits and porphyry are found in the central facies of volcanoes and low sulfidation epithermal deposits are far from central facies because in areas far from the center there can be intrusions that form a hydrothermal system so as to produce high sulfidation epithermal deposits.Research is still interpretive so it requires detailed field data, more complete laboratory data, the addition of parameters and other methods in further research. Keywords: volcanostratigraphy, volcanic facies, mineralization type, Kulon Progo